Mitochondrial protein acetylation mediates nutrient sensing of mitochondrial protein synthesis and mitonuclear protein balance. Issue 11 (15th November 2014) - Di Domenico, Antonella; Hofer, Annette; Tundo, Federica; Wenz, Tina
Abstract Changes in nutrient supply require global metabolic reprogramming to optimize the utilization of the nutrients. Mitochondria as a central component of the cellular metabolism play a key role in this adaptive process. Since mitochondria harbor their own genome, which encodes essential enzymes, mitochondrial protein synthesis is a determinant of metabolic adaptation. While regulation of cytoplasmic protein synthesis in response to metabolic challenges has been studied in great detail, mechanisms which adapt mitochondrial translation in response to metabolic challenges remain elusive. Our results suggest that the mitochondrial acetylation status controlled by Sirt3 and its proposed opponent GCN5L1 is an important regulator of the metabolic adaptation of mitochondrial translation. Moreover, both proteins modulate regulators of cytoplasmic protein synthesis as well as the mitonuclear protein balance making Sirt3 and GCN5L1 key players in synchronizing mitochondrial and cytoplasmic translation. Our results thereby highlight regulation of mitochondrial translation as a novel component in the cellular nutrient sensing scheme and identify mitochondrial acetylation as a new regulatory principle for the metabolic competence of mitochondrial protein synthesis. © 2014 IUBMB Life, 66(11):793–802, 2014